Paracrine Regulation of Thyroid-Hormone Synthesis by C Cells - Fernández-Santos, José María; Morillo-Bernal, Jesús; García-Marín, Rocío; Utrilla, José Carmelo; Martín-Lacave, Inés (IntechOpen, 2012)
None